Constructing the monstrous body in Beowulf. (26th November 2014) - Cavell, Megan
Abstract: The monstrosity of Grendel and his mother have long held the interest of Beowulf -scholars. Examining the bodily attributes of both figures in order to detect inter-textual patterns of diction, this article focuses on depictions of the monsters' skin, hands and blood. In analysing these attributes, it becomes clear that the Beowulf -poet's chosen descriptors align the monstrous body with manmade objects in general and with weapons and armour in particular. This blurring of body and human artifact creates an environment for monstrous existence that is between and outside of both human culture and nature.